LES SANZA, Collections d'instruments de musique, by Frangois Borel. Musee d'Ethnographic, Neuchatel, Switzerland, 1986. pp. 181 - Tracey, Andrew (International Library of African Music, 1987)
pages: 164-165
Keywords: African Music